Demagnetisation by crossed fields in superconductors. (25th January 2017) - Campbell, Archie; Baghdadi, Mehdi; Patel, Anup; Zhou, Difan; Huang, K Y; Shi, Yunhua; Coombs, Tim
Abstract: A study has been made of the decay of the trapped magnetisation in superconductors when exposed to a crossed field. Numerical results have been compared with the theory of Brandt and Mikitik (2002 Phys. Rev. Lett. 89 027002 ) which solves the problem for a thin strip superconductor. FlexPDE with the A formulation and COMSOL with the H formulation were both used. Simulations of a strip with a cross section aspect ratio of 20 showed good agreement with theory both for the case of a transverse field larger than the transverse penetration field and for one smaller. In the latter case the magnetisation saturates as predicted, however the simulations show a slow decay after many cycles. In the case of stacked YBCO tapes the movement of flux lines is very small and the effects of the reversible motion were investigated. This can decrease the decay initially for very thin decoupled tapes, but cause a steady decay after very large numbers of cycles. Simulations on stacked strips showed that the decay constant increased approximately linearly with the number of strips. When combined with the theory for one tape this can explain the very slow decay observed in previous experiments. Experimental results were qualitatively in agreement with theory and simulations but showed some discrepancies. However there are a number of differences between the experimental situation and theory so good agreement is not expected.